Planned home births in the region of Campinas from 2013 to 2017 (Research, Society and Development, 2021)
In recent decades, there has been an increasing number of births that are assisted by qualified health professionals and that are planned in advance to take place at home. These have been the target of discussions in the media, on social networks, among professional health councils and among the most diverse sectors of society. In this quantitative and descriptive retrospective study, we aim to analyze and describe the results of planned home births attended by a team of obstetric nurses in the city of Campinas, Brazil, from 2013 to 2017. The analyzed records were of women at usual obstetric risk, who had planned home birth attended by a team of obstetric nurses (n=160). Data were obtained by analyzing the medical records of the parturients and the variables analyzed were sociodemographic data, obstetric profile, obstetric and neonatal results. The results showed that 68.75% of the deliveries lasted up to 8 hours, 53.44% of the parturients had no perineal lacerations during the expulsion period, the postpartum maternal transfer rate was 2.52% and only 18.81% of the parturients needed intervention during the delivery process. Regarding newborns, 97.41% had a 1st minute Apgar above 8 and 100% had a 5th minute Apgar above 8. We found that the results are compatible with international studies that consider planned home births as safe as hospital births, in addition to proving the use of the precepts of humanization during childbirth, which respects the woman's choices during the physiological process of giving birth. Based on the analysis of results and comparison with literature data, we can conclude that planned home births with women at habitual obstetric risk do not offer additional risks to traditional hospital births, for both the mother and the baby.